2015
DOI: 10.1021/acsami.5b00558
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Robust Superhydrophobic Steel Surface with Anti-Icing, UV-Durability, and Corrosion Resistance Properties

Abstract: A superhydrophobic steel surface was prepared through a facile method: combining hydrogen peroxide and an acid (hydrochloric acid or nitric acid) to obtain hierarchical structures on steel, followed by a surface modification treatment. Empirical grid maps based on different volumes of H2O2/acid were presented, revealing a wettability gradient from "hydrophobic" to "rose effect" and finally to "lotus effect". Surface grafting has been demonstrated to be realized only on the oxidized area. As-prepared superhydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
306
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 533 publications
(311 citation statements)
references
References 78 publications
5
306
0
Order By: Relevance
“…[43][44][45][46][47][48][49][50][51] This is often followed by grafting low surface energy materials to achieve superhydrophobicity. Liu et al etched Mg-Li alloy using 0.1 mol/L hydrochloric acid.…”
Section: Etchingmentioning
confidence: 99%
“…[43][44][45][46][47][48][49][50][51] This is often followed by grafting low surface energy materials to achieve superhydrophobicity. Liu et al etched Mg-Li alloy using 0.1 mol/L hydrochloric acid.…”
Section: Etchingmentioning
confidence: 99%
“…It is due to destroying the coating surface by multiple gluing and de-gluing of tape on the surface. Recently, Wang et al [50] have reported a mechanically stable superhydrophobic steel surface which endured its surface microstructure against the 70 times adhesive tape peeling tests.…”
Section: Wetting Stability Of the Coatings Under Perturbation Conditionsmentioning
confidence: 99%
“…The anticorrosion performance can nearly result from the air pockets trapped in the knobbly structure. 37,38 Because of the surface tension between water and the hydrophobic hierarchical structures, it was difficult for water to penetrate the superhydrophobic layer when the sample steel was put into 3·5 wt.% sodium chloride solution. Thus, an air protection shield function is found and the corrosive medium is blocked from the superhydrophobic steel surface.…”
Section: Corrosion Inhibition Performancementioning
confidence: 99%